2010
DOI: 10.1111/j.1365-2184.2010.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia dynamics in a case of T‐LGL lymphoproliferation illustrate rapid turnover of granulocyte progenitors

Abstract: These findings illustrate how the deleterious effect of T-LGL on neutrophils is balanced, over periods of years, by pulses of compensatory neutrophil production, potentially accounting for the commonly observed prolonged indolent course of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A critical issue is to be able to affirm that the observed convergence of bisecting lines in various proliferation series is a consequence solely of chaotic dynamics; this is particularly important because there always are some stochastic components in experimental data. In our previous experimental observations, we checked the dispersion (means and sd) of the intersections, and used the Monte-Carlo technique of surrogate data to help distinguish between random and deterministic fluctuations [14] – [16, and Appendix S1 ]. Mathematicians in the field exploit various techniques of analysis involving either surrogate data [22] , [23] , or the forecasting error technique [24] , or the confinement technique [25] , with extended series of data to affirm the chaotic or stochastic nature of fluctuations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A critical issue is to be able to affirm that the observed convergence of bisecting lines in various proliferation series is a consequence solely of chaotic dynamics; this is particularly important because there always are some stochastic components in experimental data. In our previous experimental observations, we checked the dispersion (means and sd) of the intersections, and used the Monte-Carlo technique of surrogate data to help distinguish between random and deterministic fluctuations [14] – [16, and Appendix S1 ]. Mathematicians in the field exploit various techniques of analysis involving either surrogate data [22] , [23] , or the forecasting error technique [24] , or the confinement technique [25] , with extended series of data to affirm the chaotic or stochastic nature of fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…Using this method, we detected a deterministic structure, an attracting fixed-point, in various time-series, both in vitro and in vivo . We detected such focal points in: i) the cultured rat liver cancer cell line Fao, which is clonal in origin [14] ; ii) various series of primary cultures of mouse bone marrow cells, and in their derived blood progenitors [15] ; and iii) circulating human neutrophils in vivo , in a patient presenting with a T-cell lymphoma [16] . In cultured cells, experimental culture conditions were kept as constant as possible.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of leukemic LGL infiltration in the bone marrow does not correlate with degree of cytopenia. Analysis of the neutrophil population in a T-LGL leukemia patient with neutropenia showed that a decrease of neutrophil count caused by TLGLs is balanced by pulses of compensatory neutrophils production [58].…”
Section: Potential Mechanisms Of Cytopenias In T/natural Killer-largementioning
confidence: 99%
“…LGLL patients are characterized by a heterogenous clinical course. They may remain asymptomatic for a long time, but roughly 2/3 of them develop symptoms during the natural history of the disease, with 30-70% of cases requiring therapy [50,74,75]. According to current concepts, treatment of LGLL patients is required in the presence of symptomatic or severe (ANC < 0.5 × 10 9 /L) neutropenia, symptomatic or transfusion-dependent anemia and associated autoimmune conditions [76].…”
Section: Treatment Indications For Neutropenic Lgll Patientsmentioning
confidence: 99%
“…Both MTX and CyA can be maintained indefinitely, according to their tolerance. In contrast, CTX should not be used for periods longer than 6-12 months because of its mutagenic potential [75]. Regardless of the treatment status, patients should be routinely monitored for symptoms and disease progression.…”
Section: Immunosuppressive Therapymentioning
confidence: 99%